SINTESA TEORI KONSTRUKSI SOSIAL REALITAS DAN KONSTRUKSI SOSIAL MEDIA MASSA - Hadiwijaya, Achmad Suhendra (Universitas Islam Syekh Yusuf, 2023)
The theory of the social construction of reality and the theory of the social construction of mass media are still partially discussed. Several previous pieces of research have not yet correlated, elaborated, or synthesized from the theoretical aspect. Even though much has been said about the social construction of reality, media consumers are heavily influenced by media